Treatment modalities in zygomatic complex fractures: A prospective short clinical study - Ramesh Candamourty; Vinod Narayanan; M F Baig; M R Muthusekar; Manoj Kumar Jain; Ramesh M. R. Babu (Wolters Kluwer Medknow Publications, 2013)
Introduction: Zygomatic complex fractures or the tetrapod fractures are common to occur followed by the nasal bone fractures because of its prominent location. At the same time, it is difficult to obtain perfect reduction and contour postoperatively because of its complex involvement with four bones namely maxillary, temporal, orbital and greater wing of sphenoid bone. Various classifications have been put forward for better understanding and planning of treatment protocol. Aim: This study aims at comparing the following variables after reduction and fixation of fracture zygomatic complex; 1. Esthetics 2. Restoration of anatomical form 3. Occlusion 4. Function 5. Neurological deficits. Materials and Methods: Twenty patients were selected following a clinical and radiographic examination of fracture of the zygomatic complex. Reduction techniques used were Gillie's, Dingman's lateral eyebrow, and upper buccal sulcus approaches. Fixation was done at single-point or two-point or three-point protocol by transosseous wiring or miniplate osteosynthesis. Results: Among the twenty cases treated, all were males. Age distribution of the patients was between 20-60 years with a mean age of 39.5 years. There was facial asymmetry in four cases postoperatively and two among them did not follow postoperative instructions. Conclusions: Closed reduction namely Gillie's temporal approach was found to be the best reduction technique and the protocol of three point, miniplate fixation was effective in terms of stability and relapse.